Depressive symptomatology in adolescents with primary headache - Freitas, Dayzene da Silva; Costa, Clarice Nicéas Barreto da; Siqueira, Gisela Rocha; Valença, Marcelo Moraes; Oliveira, Daniella Araújo de (Headache Medicine, 2013)
Objective: The study aimed to investigate the relationship between depressive symptoms and primary headache in adolescents. Methods: 117 students (68 girls) of Public School from Recife, aged between 11 and 17 years (14.0 ± 1.7 years), were evaluated. To sort out the primary headache, was used the diagnose criteria by the International Headache Society (ICHD-II) and for tracing of depressive symptoms was used The Children's Depression Inventory. Results: There was no statistical association between the presence of depressive symptoms and headache in the last month, in adolescents with headache [66/80 (82.5%)] compared to those without headache [30/37 (81.1%)], p> 0.05, χ2]. 68.4% of the sample reported headache in the last month, 53/68 (77.9%) girls and 27/49 (55.1%) boys. Depressive symptomatology was observed on 96/117 (82.1%) students [62/68 (91.2%) girls and 34/49 (69.4%) boys, p = 0.003, χ2]. Girls had higher averages in the fields interpersonal problems p = 0021; depressed mood p = 0.013; ineffectiveness p = 0.024 and negative self-esteem p < 0.001. Conclusion: Primary headache and depressive symptoms are common among adolescents studied, but there was no association between these two conditions.